2010
DOI: 10.1371/journal.ppat.1000747
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ Lymphocytes Control Viral Replication in SIVmac239-Infected Rhesus Macaques without Decreasing the Lifespan of Productively Infected Cells

Abstract: While CD8+ T cells are clearly important in controlling virus replication during HIV and SIV infections, the mechanisms underlying this antiviral effect remain poorly understood. In this study, we assessed the in vivo effect of CD8+ lymphocyte depletion on the lifespan of productively infected cells during chronic SIVmac239 infection of rhesus macaques. We treated two groups of animals that were either CD8+ lymphocyte-depleted or controls with antiretroviral therapy, and used mathematical modeling to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
225
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(267 citation statements)
references
References 54 publications
32
225
5
Order By: Relevance
“…The finding that escape rates are generally slow [7] and other observations [42,43] have lead to a controversy in the field as to what extent CTLs are important in controlling HIV replication [44,46 -48]. Our results provide some insights into this ongoing debate as we show that slow escape rates do not necessarily imply a weak selection pressure of CTL clones.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The finding that escape rates are generally slow [7] and other observations [42,43] have lead to a controversy in the field as to what extent CTLs are important in controlling HIV replication [44,46 -48]. Our results provide some insights into this ongoing debate as we show that slow escape rates do not necessarily imply a weak selection pressure of CTL clones.…”
Section: Discussionsupporting
confidence: 49%
“…k P ¼ 0) [41]. Such a mechanism can serve as an explanation for recent experiments that have shown that CTLs do not substantially contribute to the clearance of cells during the virusproducing stage [42,43]. We attempt to make a fair comparison between the two stages by restricting the total death rate at each stage to reflect the death rate of infected cells that is observed during antiretroviral drug treatment ( [24]).…”
Section: Results (A) Hiv Dynamics With Multiple Infections Of Cellsmentioning
confidence: 99%
“…The ability to kill CD4 þ T cells in culture is consistent with the short half-life of virus in the blood after the initiation of therapy Wei et al 1995). That this is in large part a virologic effect is seen by the fact that the decay of virus in the blood goes on at a similar rate in the presence or absence of CD8 þ cytotoxic T cells (Klatt et al 2010). In addition to the direct killing of infected cells, a number of mechanisms have been proposed that result in indirect killing of uninfected cells because of their proximity to infected cells and the general state of immune activation (Lackner et al 2011).…”
Section: Mechanism Of Cell Killingsupporting
confidence: 53%
“…Healthy asymptomatic individuals, particularly LTSs, exhibit increased frequencies of the CD8 1 cells that mediate CNAR in comparison to those who progress to AIDS [46,47]. Moreover, studies of SIV-infected rhesus monkeys depleted of CD8 1 cells in vivo suggest that the virus level is maintained by a CD8 1 cell noncytotoxic process [48,49]. Also, CNAR appears to protect HESNs from infection via sexual contact [50] and children born to infected mothers [51].…”
Section: Regulatory T (T Reg ) Cellsmentioning
confidence: 99%